Evaluation of Biological Effects and Toxicity of Cetyltrimethylammonium Bromide Stabilized Silver Nanoparticles and Cetyltrimethylammonium Bromide Alone Following Intravenous Injection in Mice - Aula, Sangeetha; Lakkireddy, Samyuktha; Kapley, Atya; Hebalkar, Neha; Sharma, Rakesh K.; Uppin, Shantveer G.; Jamil, Kaiser (Current Nanomedicine, 2021)
Background: The exciting benefits of Silver nanoparticles (AgNPs) in the biomedical field necessitate generating knowledge on the safety concerns which have been raised over the applications of these NPs. Objective: To understand the biological effects and mechanism of toxicity induction of Cetyltrimethylammonium bromide (CTAB) stabilized AgNPs as well as CTAB alone in mice following intravenous injection. Methods: The investigations were carried out by measuring hematological and serum biochemical parameters, oxidative stress, genotoxicity, and histopathology. Results: AgNPs’ treatment was found to induce a marked decrease (p<0.05) in platelet and lymphocyte count, Serum glutamate oxaloacetate transaminase (SGOT), and an increase (p<0.05) in granulocytes count and Serum glutamate pyruvate transaminase (SGPT) whereas CTAB treatment-induced a decrease in platelet count. The decrease in glutathione (GSH) and an increase in lipid peroxidation (LPO) levels in the liver, spleen, and kidney of mice suggest the potential role of AgNPs in inducing oxidative stress. Genotoxicity was apparent from the increased comet parameters and micronuclei formation observed in the liver, spleen, and kidney of mice treated with AgNPs and CTAB. Histological examination in mice treated with AgNPs and CTAB showed diffused venous congestion and focal venous congestion respectively in the liver, while mild red pulp congestion in the spleen and acute tubular necrosis in the kidney were also observed. Conclusion: There is a need to develop methods to dissolve the toxicity of CTAB, thereby it inducing relatively low or no toxicity without compromising the stability of nanosilver formation. Such insights are believed to be fundamental in the synthesis of high-performance AgNPs demonstrated for outstanding biomedical applications.
Keywords: Silver nanoparticles